The Commitment of Healthcare Workers to the WHO Infection Control Principles in Tripoli, Libya - Sana Masud; Arij Mousa; Hamza Ghanaim; Nora Karim (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and objective. It is well known that health facilities are the most common places for infection and the healthcare workers are a major reason to limit its spread. Thus, all health care workers should have adequate information about the proper infection control procedures. Therefore, this study was aimed to find out the extent of the commitment of workers in Libyan health facilities to fight infection. Methods. A descriptive study was collected from a specific sample using a questionnaire in which data were collected from various health facilities. The questionnaire was consisting of 45 questions. The study was done in 2020. The result was analyzed by using excel program. Results. The results showed that 67% of healthcare workers adhere to infection control principles, while 33% do not adhere to them. Most workers responded that the excuses discourage them from applying were lack of time, lack of oversight and punishment, and shortage of personal equipment. Conclusion. The study recommended providing educational and training programs for employees, providing them with the required knowledge and skills regarding their importance in the health facility, and providing the necessary capabilities for their support and commitment for infection control programs.